The Use of Mobile Assisted Language Learning (MALL) for Teaching and Learning of EFL Students - Zakaria Bintang Pamungkas (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Education system should use technology. The domination of technology had influenced in all human aspects especially education. In modern Education, both language learning and technology influence by each other. Many variations of English language teaching and learning activity improve English language skill combined with appropriate teaching tool or media. Mobile assisted language learning as one of sophisticated technological tool in education performs many advantages to teach English language learning for improving students English skills. Moreover, English lecturers prefer to utilize it to teach English for Islamic Studies. This research was qualitative research. It was conducted at Islamic Institute of Riyadlotul Mujahidin Ngabar Ponorogo. The subjects were second semester students of Islamic Religious Education department and this reserach only focused on teaching English for Islamic Studies used Mobile Assisted Language Learning. The data in this research was collected by interview, documentation and observation. The research showed that the implementation of Mobile Assisted Language Learning had given students’ opportunity to understand English for Islamic studies material through several applications in android system. Those applications are U Dictionary, Google, Youtube, Thesaurus,Pdf Reader and Whats app. Mobile Assisted Language Learning support teaching English for Islamic Studies determined from the following indications: firstly, students really enjoyed and were more enthusiastic in learning process. Second, they understood easily about English for Islamic Studies material. Then, younger students prefer a modern style in English language learning. The last, English language communication between teacher and students had been realistically happened. The obstruction was about the cell phone signal. To maximize the use of global digital learning, this article eventually persuades that MALL is implemented for EFL teaching and learning particularly for teaching English for Islamic Studies at Islamic Higher Education.